The benefit segmentation sharia tourism in Indonesia - Sumadi, Sumadi; Sari, Octavia Gandra (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This study aims to determine the priorities and benefits sought by Muslim consumers for sharia tourism in Indonesia. The study population was the potential tourist consumer, and convenience sampling methods carried out the sampling. Methodology – The data were collected by field surveys with a sample of 300 respondents. Dendrogram cluster approach and chi-square test analysis were used to analyze the benefit segmentation. Findings – The study results explain the attributes of the tourism category to form clusters based on the reasons for the proximity of the benefits sought by consumers. Muslim tourists have a top priority for natural tourism, with the following priorities were cultural tourism, culinary tourism, and religion by sharia facilities. In terms of gender, there is no difference in the choice of the four categories of sharia tourism. Meanwhile, in terms of age and income, there is a significant difference in the choice of four categories of sharia tourism in Indonesia, with the most considerable portion choosing culinary tourism. The findings of this study imply that cluster analysis is suitable for explaining benefit segmentation. Information on the benefit of experience tourists seek an input for sharia tourism destination providers for the target market for Muslim tourists. Practical Implication – Practically the findings of this research can be used as information to develop tourism marketing strategies by the government and tourism actors with Muslim segments and target markets, both nationally and internationally. Therefore, they can formulate a marketing strategy based on demographic consideration.